2020
DOI: 10.1021/acsnano.9b05689
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Study of the Interaction of Multivalent Ligand-Modified Nanoparticles with Breast Cancer Cells with Tunable Receptor Density

Abstract: Multivalent nanoparticles that target a cell surface receptor that is overexpressed by cancer cells are a promising delivery system for cancer therapy. However, the impact of the receptor density and nanoparticle ligand valency on the cell uptake has not been studied in a system where both variables can be systematically tuned over a wide range. To address this lacuna, we report cell-uptake studies on a genetically engineered breast cancer cell line with tunable ErbB2 expression by a polypeptide micelle with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 46 publications
(150 reference statements)
1
51
0
Order By: Relevance
“…In recent research, to assess the impact of nanoparticle ligand valency and receptor density on cellular internalization, researchers have performed cell uptake studies on ErbB2-targeting, EC1 surface–functionalized micelles at five ligand valencies and 11 receptor densities [ 152 ]. They have reported that receptor density to ligand valency ratio of 0.7–4.5 and a minimum of 1.6 linkages between receptor and ligands are required to initiate cellular internalization.…”
Section: Effective Internalization Of Multivalent Drug Delivery Nanoconstructsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent research, to assess the impact of nanoparticle ligand valency and receptor density on cellular internalization, researchers have performed cell uptake studies on ErbB2-targeting, EC1 surface–functionalized micelles at five ligand valencies and 11 receptor densities [ 152 ]. They have reported that receptor density to ligand valency ratio of 0.7–4.5 and a minimum of 1.6 linkages between receptor and ligands are required to initiate cellular internalization.…”
Section: Effective Internalization Of Multivalent Drug Delivery Nanoconstructsmentioning
confidence: 99%
“…Authors have reported that the increment of ligand valence to 40-valent ErbB2 targeting peptides for a 20-nm radius nanoparticle at the ErbB2-medium and ErbB2-high levels potentiated the cellular internalization (Fig. 8 B), suggesting the use of nanocarriers with a higher valency of targeting moiety for effective drug delivery [ 152 ].
Fig.
…”
Section: Effective Internalization Of Multivalent Drug Delivery Nanoconstructsmentioning
confidence: 99%
See 1 more Smart Citation
“…Superselectivity can be applied for targeted delivery to cells with receptors that are not unique but instead are overexpressed compared to other cells. [19][20][21] The receptor density at which the selectivity is highest can be tuned by varying the interaction strength and the architecture of the particle. [22][23][24] The receptor density is directly related to the multivalent binding affinity.…”
Section: Superselectivitymentioning
confidence: 99%
“…Similarly, ELP micelles of sequence (XGVPG) 40 (SGVPG) 40 (where X is either W or V in a 1:4 ratio) have been modified to display EC1 (WTGWCLNPEESTWGFCTGSF), a targeting and internalization sequence for ErbB2, a tyrosine kinase from the epidermal growth factor receptor family. [184] Multivalent display of EC1 on the surface of these micelles increased their avidity for ErbB2, indicating their potential for targeted drug delivery as ErbB2 is overexpressed in 30% of human breast cancers. [359] Finally, Dzuricky et al [185] Multivalent peptide materials can also be used as biosensors.…”
Section: Other Applicationsmentioning
confidence: 99%